CHILDREN’S SCHOOL READINESS ENTERING ELEMENTARY SCHOOL - Anayanti Rahmawati (Early Childhood Education and Development Journal, 2019)
School readiness is the readiness that children must have to enter elementary school. School readiness includes the abilities that children need to learn well in school so that school success can be achieved. This research is a phenomenological qualitative research which aims to obtain an overview of school readiness that children have when entering the first grade of elementary school. The informants of this study were the first grade elementary school teachers totaling five people. The results of the study show that school readiness must have to be prepared early is the child's internal readiness, family readiness and school institution readiness. The child's internal readiness consists of cognitive readiness and social emotional readiness. Although cognitive readiness has been possessed by majority children, but social emotional readiness has not been fully achieved, even though it seems less attention to its achievements. This condition should not be ignored, because the realization of optimal children's internal school readiness is a combination of cognitive readiness and emotional social readiness. In addition, family preparedness and readiness of school institutions must also be sought as a form of support for children, so that children's school readiness is expected to be fully achieved optimally.